Balancing User Trust and Mental Health Outcomes: A Comparative Analysis of Data Privacy Practices in Nigerian Mental Health Apps and the EU's GDPR - Ohiro, Oghomwen Rita; Olorunfemi, Ubose Osoname (NIU Journal of Legal Studies, 2026)
The increasing use of mental health apps in Nigeria has the potential to improve access to mental health services, but this also raises concerns about data security and protection. Concerns about data privacy, lack of adequate regulation and cultural stigma in the long run chip away at users’ trust of those apps and raise doubts about their efficacy in providing support to those in need. This study examined the relationship between data privacy policies and the use of mental health apps in Nigeria, focusing on how data protection laws influence users’ attitudes. The paper examines the existing legal framework, including the Nigeria Data Protection Act 2023 and compares it with other regulatory regimes such as the General Data Protection Regulation in Europe and the Protection of Personal Information Act in South Africa. In this paper empirical research on current data collection practices and privacy issues in mental health applications are reviewed. The findings suggest that despite the considerable advances in regulations in Nigeria, there are shortcomings in law enforcement, regulations based on the industry and guidance on handling of sensitive information offered by users of mental health apps. These limitations result in a lower user trust and reduced app efficacy. The paper underscores the necessity of clarifying regulatory guidelines, adopting privacy-by-design principles, and addressing sociocultural factors to enhance the effectiveness of mental health applications in Nigeria. Keywords: Data privacy, mental health apps, user trust, personal data, privacy by design